The role of Facebook and Twitter as organisational communication platforms in relation to flood events in Northern Ireland. Issue 3 (14th November 2017) - Stephenson, J.; Vaganay, M.; Coon, D.; Cameron, R.; Hewitt, N.
Abstract : Social media networks enable flood‐affected individuals to obtain and share credible information; however, their full potential is not recognised by official institutions. This study evaluates flood‐related usage of Facebook and Twitter by organisations in Northern Ireland. Data collection involved extraction of publicly visible flood‐related Facebook and Twitter posts, over a 9‐month period, from official accounts of selected organisations. NVivo was used to conduct a content analysis of the data. The results concluded that flood‐related information are predominantly distributed at the flood response stage, illustrating the present reactive social media presence of organisations. Twitter accounted for a higher proportion of broadcasting information, while Facebook was more likely to encourage specific behaviour. Public preference was associated with information provided by emergency services and information transmitted at the response stage. Policy implications include the need for an established proactive social media presence among organisations with a flood‐related function and community consultation to identify public information needs.